FACTORS AND MAIN RISKS OF HARMFUL SUBSTANCES DISTRIBUTION IN A PRODUCTION PLANT. - Turakulova Gulasal Zohidjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In modern industrial production processes, environmental safety is becoming increasingly important. In particular, the release of harmful substances into the air during production - chemical compounds in gaseous, liquid and solid states, dust particles, toxic substances - poses a serious threat to the environment and human health. These processes have a negative impact on the health of workers, productivity and the sustainable operation of industrial enterprises in general.